Rationalising the solid-state properties of dithiadiazolyl radicals using a combined theoretical and experimental approach - Dippenaar, Alwyn Bernard (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2019.